Job satisfaction of teachers in four selected Seventh-Day Adventist schools - Faderogaya, Lily Fetalino (Animo Repository, 1989)
This study determines the level of job satisfaction of the teachers of four selected Seventh-day Adventist schools. This study made use of the descriptive method which involved recording, describing, analyzing, and interpreting the gathered data. The Pearson Correlation was used to determine if the profile of the respondents were in any way correlated to their response to the questionnaire regarding their perceived level of satisfaction toward some job factors present in their work environment. Included in this study were the teachers from the following Seventh-day Adventist schools: Pasay City Academy, Baesa Adventist Academy, Lipa Adventist Academy and Northern Luzon Academy. The respondents included all the full-time teachers in the elementary and secondary levels. Actual number of respondents totaled 62. The instruments used were the Personal Data Checklist made by the researcher and the Job Satisfaction Questionnaire originally constructed by Marcelino Magno Manuel (1981) and revised by Santiago (1982). In this study, the revised edition of Santiago was used. Findings of the study revealed that majority of the respondents were below forty six years old, female, have been teaching for less than 16 years, married and live in the urban community. In general, there were more respondents whose level of job satisfaction did not reach the satisfactory level. Only four job factors were found to be satisfactory. The rest were neither satisfactory nor dissatisfactory. Both the motivators and hygiene factors contributed to the teachers' perceived level of satisfaction or dissatisfaction. Despite the differences in the perceived level of satisfaction or dissatisfaction, the respondents generally tend to agree on some common factors that caused satisfaction or dissatisfaction to them. The causes of satisfaction were: the work itself, the responsibility and achievement that go with the work, and the relation between co-employees and administrators. The causes of dissatisfaction were the aspects related to promotion, recognition, salary and fringe benefits, working conditions, policy, supervision, and administration. As a whole, the level of job satisfaction of the respondents were very highly correlated to age and length of service. The independent variables of sex, marital status, department level, and residence community had little or sometimes no correlation at all to the respondents' level of job satisfaction.